Estudio de tres niveles de sombra sobre variables fisiologicas y reproductivas en cacao (theobroma cacao) clon eetp – 801, en la provincia de Zamora Chinchipe, el Padmi - León Ortiz, Marjory Nathaniel (2022)
Ecuador is known for producing fine and aromatic cocoa, which is highly valued by the international market for the production of fine chocolates. The country contributes with 60% of the world production of aromatic cocoa called "arriba" from the National genotype. The effect of shade in the field is very complex and the need arises to have a better knowledge to solve the problems that still arise in terms of its rational use, to maximize plant growth in its early stages during the establishment and later to increase production. The main objective of this study was to evaluate the effect of 3 levels of shade on physiological and reproductive variables in cocoa clone EETP - 801, which was carried out at the Experimental Station "El Padmi" of the UNL, in the province of Zamora Chinchipe, for a period of 6 months (November 2021 to February 2022) on a crop of cocoa clone EETP-801 of 2 years 5 months old, under a DCA arrangement with 3 treatments (0, 35 and 80% shade) and 7 replications. Physiological variables such as crown diameter were measured every 21 days, trunk cross-sectional area (ASTT) was evaluated at the beginning and end of the experiment, leaf area (FA) and leaf area index (LAI) were evaluated at the end of the trial, chlorophyll concentration and stomatal density were measured at the end of the field trial, while productive variables such as fruit length were measured every 21 days, as well as soil pH and EC. The results obtained showed that the effect on dependent variables was evaluated by ANOVA and mean test (Tukey), showing that in most of the variables there were no significant differences between treatments. However, the full light treatment allowed taller plants and the 80% shade treatment favored the increase of chlorophyll, A, B and total chlorophyll. In general, the results of the research show that the use of shade does not show statistically significant effects on physiological and productive variables of clone EETP - 801, which shows that in this area the implementation of shade would not be necessary. Key words: Theobroma cacao L, development, shade levels.